Lärdom och läsande kring sekelskiftet 1800 - Peter Josephson (Lychnos)
During the latter half of the 18th century, the doors of German universities were opened from within. Scholars abandoned Latin in favor of the vernacular and turned outward to a broader audience. Philosophers and scientists saw in the printing press a tool that would help eradicate ignorance and superstition, ultimately laying the groundwork for a better society. However, the enthusiasm was short-lived. Influential scholars increasingly lamented by the turn of the 19th century that competition for readers' attention had compromised the quality of science. Many described a situation of intellectual undercutting and warned that popular science was displacing the genuine. In "Hermeneutics for the People!", I examine the late 18th and early 19th-century German-language debate on the increasing commercialization of academic knowledge. Specifically, I analyze how one sought to stimulate demand for serious and educational literature by fostering people into good and quality-conscious readers.